PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, LIKUIDITAS DAN KEPEMILIKAN INSTITUSIONAL TERHADAP STRUKTUR MODAL - Suryani (Nusantara Hasana Journal, 2022)
The purpose of this study was to determine the effect of firm size, profitability, liquidity variables and institutional ownership of capital structure. The population in this study are plantation companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2021. The sample in this study were 11 plantation sub-sector companies listed on the Indonesia Stock Exchange for the period 2017-2021. The sample selection used purposive sampling method. This study used multiple linear regression analysis with Statistical Package for the Social Science (SPSS) version 25. The results showed that firm size had a positive and significant effect on capital structure, profitability did not influence on capital structure, while liquidity and institutional ownership have a negative and significant effect on capital structure. The results of this study also show that simultaneously firm size, liquidity, institutional ownership of the capital structure.